Gender Integration in Climate Change and Agricultural Policies: The Case of Nepal - Paudyal, Bimala Rai; Chanana, Nitya; Khatri-Chhetri, Arun; Sherpa, Lakpa; Kadariya, Ishwari; Aggarwal, Pramod K. (Frontiers Media, 2019)
Gender integration across national policy processes is critical to ensure effective implementation of climate change adaptation interventions in agriculture. This is especially so for countries like Nepal, where climate vulnerability and women participation in agriculture is high, accompanied by gender gaps in access to information, technologies, markets, and labor burden. To do this, it becomes necessary to address the inter-related issues of gender, agriculture, and climate change instead of looking at them in isolation. This study, therefore, highlights policy gaps to suggest a set of recommendations for improving gender responsiveness at policy level in Nepal. It presents the gender gaps that women face in agriculture, based on data collected from five districts of the country. Subsequently, using the concept of gender-agriculture-climate change nexus, it analyses 20 government policies and related documents of Nepal based on a set of five indicators. The policy analysis elucidates the level of gender integration in agriculture and climate change policies in the country. Eleven of the 15 agriculture related documents acknowledge the need to focus on women farmers, with nine of them also defining provisions for women-related issues in agriculture. Two of the five climate change policies merely acknowledge gender issues related to climate change. However, only two of the 20 policy documents recognize the need to address gender, climate change, and agricultural issues in coherence. Accordingly, the paper proposes a framework highlighting key points to make policy process and implementation plans in the agriculture sector more gender responsive in Nepal, focusing on the development and promotion of gender responsive Climate-Smart Agriculture technologies and practices. It suggests measures to increase access of assets and services to women farmers, improve their capacity to participate in decision making across levels, and promote transformative changes at both local and policy level.